The Influence Of Brand Image, Brand Personality And Brand Trust On Brand Loyalty For Indomie Noodle Products (Survey of Management Study Program Students at University Perjuangan Tasikmalaya) - Saputra, Gilang Eka; Pauzy, Depy Muhamad; Wibawa, Gian Riksa (Universitas Dehasen Bengkulu, 2024)
This research aims to determine the influence of Brand Image, Brand Personality and Brand Trust on Brand Loyalty of Indomie noodle products among consumers at Tasikmalaya University of Struggle students. The method used is quantitative with a research sample of 100 respondents. The data used are primary and secondary data. The analytical tool used in this research is multiple linear regression analysis using SPSS version 25. Based on the results of this research, it shows that Brand Image, Brand Personality and Brand Trust simultaneously have a positive and significant effect on Brand Loyalty. Brand Image partially has a significant effect on Brand Loyalty. Brand Personality partially has a significant effect on Brand Loyalty. Brand Trust partially has a significant effect on Brand Loyalty.